Pattern of Axial Length Growth in Children Myopic Anisometropes with Orthokeratology Treatment. (2nd July 2020) - Long, Wen; Li, Zhouyue; Hu, Yin; Cui, Dongmei; Zhai, Zhou; Yang, Xiao
ABSTRACT: Purpose: To compare the pattern of growth in axial length (AL) between children with anisometropia who wear orthokeratology (OK) lenses and those who wear spectacles (SP). Methods: A retrospective study was conducted. Data of baseline and 1 year from 252 children (8–14 years old) anisomyopes who sought refraction corrections at the Zhongshan Ophthalmic Center between October 2013 and June 2017 were reviewed. Seventy-nine unilateral myopic anisometropes (UMA) and 98 bilateral myopic anisometropes (BMA) treated with OK lenses were set as study groups (OK-UMA and OK-BMA groups). Age, refraction, and AL-matched unilateral (n = 38) and bilateral myopic anisometropes (n = 37) treated with spectacles were set as control groups (SP-UMA and SP-BMA groups). The 1-year change in AL between the study and control groups (OK-UMA vs. SP-UMA and OK-BMA vs. SP-BMA) was compared. Results: There were no significant differences in the baseline of age, refraction, and AL between OK-UMA and SP-UMA or OK-BMA and SP-BMA groups (all P > .05). Compared to the SP-UMA group, annual axial elongation of the myopic eyes of the OK-UMA group was smaller (0.05 ± 0.19 mm vs. 0.33 ± 0.29 mm, P < .001); however, AL elongation in the non-myopic eyes were comparable between SP-UMA and OK-UMA groups ( P > .05). At the end of 1 year, the interocular difference in AL (aniso-AL) decreased by 0.29 ± 0.29 mm ( P < .001) in the OK-UMA group but remained unchanged in SP-UMA group. Compared to the SP-BMA group, annual axial elongations of both eyes of the OK-BMA group were smaller (the more myopic eye, 0.05 ± 0.17 mm vs. 0.38 ± 0.21 mm; the less myopic eye, 0.15 ± 0.19 mm vs. 0.35 ± 0.28 mm; both P < .001). At the end of 1 year, aniso-AL decreased by 0.10 ± 0.15 mm ( P < .001) in the OK-BMA group but remained unchanged in the SP-BMA group. Conclusion: Orthokeratology is effective in reducing the interocular difference in AL of children anisomyopes through greater retardation of axial elongation of the more myopic eyes.